Switching Reactive Oxygen Species into Reactive Nitrogen Species by Photocleaved O2‐Released Nanoplatforms Favors Hypoxic Tumor Repression. Issue 19 (8th August 2021) - Luo, Tao; Wang, Duo; Liu, Lidong; Zhang, Yan; Han, Chuangye; Xie, Ying; Liu, Yan; Liang, Jingchen; Qiu, Guanhua; Li, Hongxue; Su, Danke; Liu, Junjie; et al.
Abstract: In various reactive oxygen species (ROS)‐based antitumor approaches (e.g., photodynamic therapy), increasing attentions are made to improve ROS level, but the short lifetime that is another decisive hurdle of ROS‐based antitumor outcomes is not even explored yet. To address it, a photocleaved O2 ‐released nanoplatform is constructed to release and switch ROS into reactive nitrogen species (RNS) for repressing hypoxic breast tumor. Systematic explorations validate that the nanoplatforms can attain continuous photocontrolled O2 release, alleviate hypoxia, and elevate ROS level. More significantly, the entrapped PDE5 inhibitor (PDE5‐i) in this nanoplatform can be enzymatically decomposed into nitric oxide that further combines with ROS to generate RNS, enabling the persistent antitumor effect since RNS features longer lifetime than ROS. Intriguingly, ROS conversion into RNS can help ROS to evade the hypoxia‐induced resistance to ROS‐based antitumor. Eventually, RNS production unlocks robust antitumor performances along with ROS elevation and hypoxia mitigation. Moreover, this extraordinary conversion from ROS into RNS also can act as a general method to solve the short lifetime of ROS. Abstract : An unprecedented solution to address the short lifetime of reactive oxygen species (ROS), i.e., switching short‐lived ROS into long‐lived reactive nitrogen species (RNS), is established and enabled by a photocleaved O2 ‐released nanoplatform. It combines with O2 release‐enhanced ROS/RNS production and hypoxia alleviation to cooperatively favor the persistent hypoxic tumor repression.